Management of chimeric antigen receptor T-cell-related toxicity of a patient affected by cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome, followed by an intestinal perforation: a case report - G. Menardi; A. Castellino; C. Castellino; M. E. Bersia; E. Grande; G. Fraternali; M. Massaia; C. Fruttero (Journal of Medical Case Reports)
Abstract Background Mantle cell lymphoma is a diverse B-cell lymphoma with varying clinical behaviors. Treating relapsed or refractory mantle cell lymphoma is challenging, with Bruton’s tyrosine kinase inhibitors proving effective but not curative. Post-Bruton’s tyrosine kinase inhibitor failure, the prognosis remains unfavorable. Brexucabtagene autoleucel, a US Food and Drug and European Medicines Agency-approved anti-CD19 chimeric antigen receptor T-cell therapy, marks a significant breakthrough offering hope in this challenging scenario. Case presentation This article presents an analysis of the management of short-term chimeric antigen receptor T-cell therapy-associated toxicities, focusing on a specific case of a patient with refractory mantle cell lymphoma. The report underscores the complexities of chimeric antigen receptor T-cell treatment and sheds light on strategies employed to mitigate toxic effects. The case involves a white Caucasian 59-year-old male affected by relapsed mantle cell lymphoma who underwent various treatments, including autologous anti-CD19 chimeric antigen receptor T-cell therapy (brexucabtagene autoleucel). The patient experienced immune effector cell-associated hematotoxicity along with cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome, necessitating intervention. The management involved a combination of tocilizumab, corticosteroids, and anakinra, which effectively alleviated symptoms. Additionally, the article highlights the patient’s case of intestinal perforation following CAR-T therapy. Although there is a correlation between gastrointestinal perforation and interleukin 6 receptor inhibitors, the adverse event was attributed to the patient’s preexisting diverticulitis and the immunosuppressive drugs administered leading to cytomegalovirus reactivation. The study emphasizes the evolving landscape of chimeric antigen receptor T-cell therapy and the significance of addressing toxicities associated with this innovative treatment approach. It underscores the value of anakinra as a potential corticosteroid-sparing therapy for immune effector cell-associated neurotoxicity syndrome and raises the need for further research to optimize the management of immune effector cell-associated hematotoxicity and associated complications. The potential preventive use of drugs to mitigate toxicities also warrants exploration, albeit with the current dearth of evidence. Conclusions In conclusion, this article offers valuable insights into the challenges of managing chimeric antigen receptor T-cell-related toxicities through a detailed case presentation and highlights the significance of adopting multidisciplinary approaches to enhance patient outcomes and safety. Further research is needed to refine strategies and advance the understanding of these complex treatment-associated toxicities.